2017
DOI: 10.1371/journal.pone.0179537
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of infectious diseases in asylum seekers at a tertiary care hospital in Switzerland

Abstract: ObjectiveThe increasing number of refugees seeking asylum in Europe in recent years poses new challenges for the healthcare systems in the destination countries. The goal of the study was to describe the evolution of medical problems of asylum seekers at a tertiary care centre in Switzerland.MethodsAt the University Hospital Basel, we compared all asylum seekers during two 1-year time periods in 2004/05 and 2014/15 concerning demographic characteristics and reasons for referrals and hospitalizations.ResultsHun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
2
20
0
2
Order By: Relevance
“…Within Europe, there is an increasing population of refugees seeking asylum, often those displaced from areas of Africa or the Middle East due to conflict. These are vulnerable populations, and individuals are at risk of contracting a number of important infectious diseases, in addition to scabies, which frequently coexist [41]. A recent observational study of scabies outbreaks, in residential and nursing care homes in south-east England, showed that the clinical presentation of scabies in this elderly population differs from the classic descriptions with which clinicians are familiar.…”
Section: The Impact Of Scabiesmentioning
confidence: 99%
“…Within Europe, there is an increasing population of refugees seeking asylum, often those displaced from areas of Africa or the Middle East due to conflict. These are vulnerable populations, and individuals are at risk of contracting a number of important infectious diseases, in addition to scabies, which frequently coexist [41]. A recent observational study of scabies outbreaks, in residential and nursing care homes in south-east England, showed that the clinical presentation of scabies in this elderly population differs from the classic descriptions with which clinicians are familiar.…”
Section: The Impact Of Scabiesmentioning
confidence: 99%
“…Recognized examples include disadvantaged Indigenous populations within Australia, New Zealand and Canada, 26,60-62 imprisoned 63,64 and homeless populations, 65 and among groups seeking asylum within Europe. [66][67][68] Scabies is a disease of poverty and inequity and it is likely that sub-populations with higher burdens would be found in many otherwise high-income settings. 69 Institutional scabies outbreaks result in considerable morbidity, stigma and healthcare cost in high-income settings.…”
Section: Epidemiology and Mappingmentioning
confidence: 99%
“…56,58 Pneumonia and skin infections were commonly identified infectious diseases leading to ED consultations and admission to hospital in European centers. 63 However, chronic infections are particularly important. Tuberculosis has a much higher incidence in newly arrived asylum seekers, especially from Eritrea and Pakistan, than in the native European population.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…Isolation precautions were indicated in almost one-third of the patients. 63 However, rare parasitic diseases like neurocysticercosis were also found in refugees from Burma presenting with severe occipital headache at an ED in the United States. 65 A further concern with chronic health issues is the emergence of multiresistant bacteria in refugees from the Middle East.…”
Section: Infectious Diseasesmentioning
confidence: 99%